An overview of benefits and challenges of building information modelling (BIM) adoption in UK residential projects. Issue 3 (7th July 2019) - Georgiadou, Maria Christina
Abstract : Purpose: This paper aims to present a state-of-the-art review of building information modelling (BIM) in the UK construction practice. In particular, the aim is to examine the scope, value and practical implications of BIM implementation in residential projects by evaluating practitioners' perspectives working in the Greater London Area (GLA). Design/methodology/approach: The paper outlines the general status quo of BIM adoption and maturity in the UK. It then discusses the feasibility of BIM use in residential projects drawing on an online survey and complementary semi-structured interviews with building professionals. The cross-comparison between the evidence base and literature review uncovers the specific benefits, challenges and risks to BIM implementation in the house building sector. Findings: BIM is an evaluation methodology that helps the management of digital information throughout the project lifecycle. At a conceptual level, a BIM-enabled project offers quality assurance and on-time delivery, collaboration and communication improvement, visual representation and clash detection and whole lifecycle value. The findings, however, suggest that the most frequently reported benefits are related to collaboration and the blend of product (software) and process innovation, whilst lifecycle thinking and waste reduction are often overlooked. At present, there is widespread awareness on BIM but with a financial barrier to invest in developing digital capabilities, particularly for small- and medium-sized enterprises. Practical implications: The paper concludes with a critical commentary on the lack of strategic leadership in both the supply and demand side. The role of policy to streamline commercial drivers for whole lifecycle costing in procurement is endorsed to drive the change management required to address the short-term mind-set of senior management and wider fragmentation of the construction industry, also serving as a research question for further research and development in the field. Originality/value: There are relatively few studies evaluating BIM perspectives in UK residential projects. This paper explores the feasibility and "real-life" value of BIM in housing practice, drawing on views and experiences of building professionals in GLA. In particular, the research findings provide an evidence base evaluating the extent to which the house building industry has the expertise and capability to operate in a BIM environment and to comply with the Level 2 mandate and explore which of the generic barriers and drivers of BIM-readiness are more relevant to the design and construction of housing projects.